Population dynamics of Ectatomma planidens (Hymenoptera: Formicidae) under laboratory conditions - Antonialli Jr., William F.; Tofolo, Viviane Cristina [UNESP]; Giannotti, Edilberto [UNESP] (My University, 2007)
The ant Ectatomma planidens belongs to the subfamily Ectatomminae and it is abundantly found in the Neotropical region. Five colonies of such species were studied regarding their population dynamics in the laboratory, aiming to generate life tables and determine the entropy. The life expectancy curve of the workers indicated that in the first age interval, the value of e x = 142.55 approached the mean longevity of such workers (188.23 ± 110.99 days). Upon reaching this mean longevity, there was a greater decline in the life expectancy, which tends to decrease gradually with the time. The value found for entropy was H = 0.739 (between 0.5 and 1.0), and the survival pattern of these individuals was characterized by high mortality in the first intervals and growing life expectancy as time went by.
Keywords: Ectatomma planidens; Entropy; Life expectancy; Mean longevity; Ectatomminae; Formicidae; Hymenoptera